Age-adjustment of insulin pump settings in children and adolescents with type 1 diabetes mellitus - Dmitriy Nikitich Laptev; Yury Ivanovich Filippov; Andrey Olegovich Emel'yanov; Tamara Leonidovna Kuraeva (Сахарный диабет, 2013)
AIM: This study was aimed at investigation of daily glycemic variations in children and adolescents with type 1 diabetes mellitus (T1DM) on continuous subcutaneous insulin infusion (CSII) in order to define in greater detail the correlation of said parameters with periods of age to the end of improving current recommendations for pump settings adjustment. MATERIALS AND METHODS: 138 children and adolescents aged 1?18 years on CSII therapy took part in this study. Patients were subdivided into three groups according to their age: preschool children (n=23), prepubertal children aged <12 years (n=39) and teenagers up to 18 years old (n=76). CSII regimens were analyzed in every group, including average daily insulin dose, basal-to-bolus ratio, daily basal profiles, carbohydrate ratio (CR) and insulin sensitivity factor (ISF). RESULTS: Daily requirement for both basal and bolus insulin does differ between ages. Youngest children require higher basal infusion rate during evening hours and first half of the nighttime while demonstrating least requirement at daytime. Instead, prepubertal children and adolescents require higher basal infusion rate during early morning hours. We also show CR and ISF to be dependent of daytime in all studied age grades. CONCLUSIONS: Basal-to-bolus ratio along with circadian variability in requirement for insulin are clearly governed by patient's age. Importantly, the ratios for bolus calculations, developed from our data, significantly differ from those provided by popular formulas, suggesting the latter be modified into taking regard of the age grade for proper individual adjustment of pump settings.